Analisis terhadap Model Layanan Mobile Banking pada Bank Syariah Indonesia dari Tinjauan Konsep Syariah - Annas Syamsu Fahmi Rizal; Ahmad Muqorobin; M Qoshid Al Hadi; Mohammad Syifa Urrosyidin (Mumtaz Publishing, 2025)
During the post-COVID-19 pandemic recovery period, rapidly developing information technology in recent years has directed the focus of several banks towards digital services, including through mobile banking applications. The rapid growth of the internet has changed the way companies connect with customers, as well as the banking business in Indonesia. The concept of